Artykuł recenzyjny monografii Łukasza Dubińskiego i Przemysława Zdyba, Zbieg egzekucji sądowej i administracyjnej, Wydawnictwo Currenda, Sopot 2023, ISBN: 978-83-65966-58-2, ss. 153 - Dominika Skoczylas (Studia Administracyjne)
The aim of the review article is to analyze the research issues in the area of ​​the intersection of judicial and administrative enforcement presented in the monograph by Łukasz Dubiński and Przemysław Zdyb entitled "The confluence of judicial and administrative enforcement". The analysis will cover both the research issues undertaken by the authors, as well as the structure of the work and the research methods adopted. The provisions regarding the confluence of administrative enforcement are regulated in Chapter 5 of the Act on Enforcement Proceedings in Administration, entitled "Confluence of Enforcement ”, while judicial enforcement in Article 773 of the Code of Civil Procedure. The choice of research topic made by the authors should be considered fully justified, primarily due to the existing legal problems regarding the resolution of the combination of administrative and judicial enforcement representatives of the doctrine and also contribute to explaining the course of proceedings and how to eliminate the coincidence of executions depending on the procedural situation.